The Influence of Power Distance on the Communication Effectiveness of Indonesian Workers - Ditya Hanun Aqila; Najwa Zarka; Nadia Octa Safitri; Julita Adianti; Dana Azizah Rahmat (Journal of Digital Business and Innovation Management, 2026)
This study aims to examine the influence of power distance on the communication effectiveness of Indonesian migrant workers in international multicultural workplaces. The study employed a quantitative approach using a survey design. Data were collected through online questionnaires distributed to Indonesian workers who had experience working abroad. A total of 107 responses were obtained, and after outlier screening using the Z-score method, 101 valid responses were analyzed. The research instruments were tested using validity and reliability tests, showing that all items were valid and reliable with Cronbach’s Alpha values above 0.70. Because the data did not fully meet the normality assumption, hypothesis testing was conducted using the bootstrap method with 1000 resampling iterations. The results showed that power distance had a negative but statistically insignificant effect on communication effectiveness, with a regression coefficient value of -0.047 and a significance value of 0.211 (>0.05). The coefficient of determination (R²) value was 0.011, indicating that power distance explained only 1.1% of communication effectiveness, while the remaining 98.9% was influenced by other factors outside the study. Therefore, it can be concluded that power distance is not a major factor affecting the communication effectiveness of Indonesian workers abroad.